AISTIKHDAM AINISTIQRAM FI TANMIAT MAHARAT ALKITABA - Andri Setiadi; Fitri Annisa Febriana; Rizal Firdaus (SHAWTUL ARAB, 2024)
Online education or via social media is one of the changes in education methods and strategies that are very different from what they were before. One of the popular social media outlets in the world of education is Instagram. The purpose of this research is to know the use of Instagram in developing writing skills and how to benefit from this program. In this qualitative research, the researcher followed the descriptive analytical method and followed the observation method to collect data and the Mills and Huberman method in analyzing the data, which is classifying, presenting, and concluding the data. This research proved that instagram can be used to develop students’ writing skills because Instagram is one of the most widely used social media tools for them and suits their age stage. Among the features on Instagram that can be used to develop writing skills are Instagram Feed and Instagram Story, but the use of Instagram in this field is only outside the classroom to finish assignments